2016
DOI: 10.3171/2015.12.focus15572
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of combined intraoperative electrophysiological investigation with 3-T intraoperative MRI for awake cerebral glioma surgery: comprehensive review of the clinical implications and radiological outcomes

Abstract: OBJECTIVE This study aimed to assess the clinical efficiency of combined awake craniotomy with 3-T intraoperative MRI (iMRI)–guided resection of gliomas adjacent to eloquent cortex performed at a single center. It also sought to explore the contribution of iMRI to surgeons' learning process of maximal safe resection of gliomas. METHODS All patients who underwent an awake craniotomy and iMRI for resection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 37 publications
2
37
0
Order By: Relevance
“…We looked with interest at some pioneering papers about the feasibility of combining 2 among the most powerful aids available: the ioMRI (for morphology) and the awake surgery (for function) 18, 20, 31, 32, 33, 34, 35. We were particularly impressed by the recent series of Ghinda et al 35 . of 106 patients with gliomas in eloquent areas, operated on with awake intraoperative mapping and high-field (3T) ioMRI: they reported GTR rates of 89% and 96% for LGG and HGG, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…We looked with interest at some pioneering papers about the feasibility of combining 2 among the most powerful aids available: the ioMRI (for morphology) and the awake surgery (for function) 18, 20, 31, 32, 33, 34, 35. We were particularly impressed by the recent series of Ghinda et al 35 . of 106 patients with gliomas in eloquent areas, operated on with awake intraoperative mapping and high-field (3T) ioMRI: they reported GTR rates of 89% and 96% for LGG and HGG, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The largest series to date, published by Ghinda et al [41], demonstrated that the combined use of iMRI with mapping allowed for the safe increase in the extent of resection and suggested a survival benefit from maximal resection of both low-and high-grade gliomas. The majority of studies combining these 2 techniques have used 1.5-T magnets [3,[42][43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…Glioblastoma multiforme (GBM) is a primary malignant adult brain tumor with extremely poor prognosis (Ostrom et al, 2017). Current therapies such as surgery and chemo-and/or radiotherapy only provide palliative care resulting in median GBM patient survival of about 14-15 months (Ghinda et al, 2016). Using patient samples, efforts to identify underlying genetic aberrations that lead to GBM have resulted in the identification of genomic amplification of EGFR, PDGFRA, and FGFR; along with activating mutations and overexpression of Receptor Tyrosine Kinases (RTKs) and genes of the PI3K pathway.…”
Section: Introductionmentioning
confidence: 99%